REHABILITATION OF LUMBAR SPINAL DEVIATIONS USING AQUATIC EXERCISES: A STUDY ON STUDENTS OF THE TECHNICAL INSTITUTE IN AL-DIWANIYAH GOVERNORATE - Dr. Nawfal Dakhil (Galaxy International Interdisciplinary Research Journal, 2024)
This study investigates the effectiveness of aquatic exercises in rehabilitating lumbar spinal deviations among students at the Technical Institute in Al-Diwaniyah Governorate. Lumbar spinal deviations, such as lordosis, kyphosis, and scoliosis, are prevalent conditions affecting the student population, often leading to musculoskeletal issues and reduced quality of life. The research employs a structured aquatic exercise program designed to address these deviations, utilizing the buoyancy and resistance properties of water. The study involves a sample of students with diagnosed lumbar spinal deviations who participate in a supervised aquatic exercise intervention over a specified period. Pre- and post-intervention assessments include clinical evaluations, imaging studies, and subjective reports from participants. The research aims to measure the impact of aquatic exercises on spinal alignment, muscle strength, and overall functional improvement. Preliminary findings suggest that aquatic exercises contribute positively to the rehabilitation of lumbar spinal deviations, offering a low-impact and supportive environment for targeted exercises. The outcomes of this study hold significance for designing comprehensive rehabilitation programs in educational settings, emphasizing the potential of aquatic exercises as a valuable therapeutic modality for addressing lumbar spinal deviations and promoting overall musculoskeletal health in student populations.